2013
DOI: 10.3892/or.2013.2846
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and quantitative analysis of BCL6 expression in human colorectal carcinogenesis

Abstract: Abstract. The aim of the present study was to determine whether BCL6 is expressed during malignant transformation of the large bowel and to assess whether, and to what extent, immunoreactivity is related to the different stages of neoplastic progression. Samples of normal colorectal mucosa (n=22), microadenomas (n=22) and colorectal cancer (n=22), were analyzed by immunohistochemistry, immunofluorescence coupled with confocal microscopy and western blotting. Our results clearly outlined the marked increase occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…2a). The occurrence of BCL6 in both cell compartments was also observed in microadenoma and colorectal cancer cells [32]. In general, protein translation takes place predominantly in the extranuclear cell compartment [33].…”
Section: Discussionmentioning
confidence: 99%
“…2a). The occurrence of BCL6 in both cell compartments was also observed in microadenoma and colorectal cancer cells [32]. In general, protein translation takes place predominantly in the extranuclear cell compartment [33].…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly BCL6 protein has been found in solid malignancies, including squamous cell carcinoma [6] colorectal [7] gallbladder [8], and breast cancer [9]. In most cases, BCL6 expression is associated with poor prognosis and worse outcome, although not always-BCL6 can suppress tumorigenesis in medulloblastoma [10] and is associated with a better prognosis in a subset of gastric lymphoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…B-cell CLL/lymphoma 6 (BCL6), a highly conserved zinc finger (ZF) transcriptional factor, was first identified as an oncogene by gene expression profile in non-Hodgkin's lymphoma in 2000; 3 it exhibits pivotal roles in germinal center formation and regulation of lymphocyte function, differentiation, and survival. 4 In recent years, more and more studies identified that BCL6 was overexpressed not only in B-cell lymphoma 5 but also in gastric cancer, 6 gallbladder cancer, 7 breast cancer, 8 colorectal cancer, 9 head and neck cancer, 10 and so on. However, there are quite a few studies on the function of BCL6 in ovarian cancer, and it remains unclear whether BCL6 may aberrantly express or be a potential prognosis marker in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%